Analisis Pengaruh Risk Based Capital, Profitabilitas dan Likuiditas Terhadap Financial Distress: Studi Kasus Perusahaan Asuransi di Bursa Efek Indonesia Tahun 2018 -2022 - Nia Fitriah Dharmawati; Anita Akhirruddin (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
This study aims to determine the effect of risk based capital, profitability and liquidity on financial distress of insurance companies listed on the Indonesia Stock Exchange in 2018 - 2022. This research uses a quantitative approach. Sampling using purposive sampling, after selection, 11 companies were obtained with an observation time of 5 years so that the observation object was 55 samples. The analysis technique used is multiple linear regression analysis with the help of the SPSS 24 program. The results showed that risk-based capital, profitability and liquidity simultaneously affect financial distress. While partially risk-based capital has no significant effect, profitability and liquidity have a significant effect on financial distress.